Introduction of a new nomen-clature of academic specialities in Russia: Continuity and innovations - S. I. Pakhomov; V. A. Gurtov; A. V. Stasevich (Russian State Vocational Pedagogical University, 2021)
Introduction. The nomenclature of academic specialities to be awarded academic degrees is a system-forming element of academic degree holders' certification system in any country of the world. Therefore, there is a need to revise and update the relevant structure of academic specialities in order to meet the prospective demand from research and development sector of high-tech industries. Apparently, the current nomenclature of 2017, as the instrument of realisation of public policy in the sphere of the state certification of academic and teaching staff in Russia, needed updating.The aim of the present research was to analyse a new version of the nomenclature of academic specialities in Russia to be awarded the degree of Doctor or Candidate of Science, and to make conceptual proposals on the implementation of new nomenclature provisions taking into account possible transformation of scientific and educational environment, including the emergence of new complex areas of academic research.Methodology and research methods. The research object is a system of certification of academic and teaching staff from the position of a three-level structure of the nomenclature of academic specialities, according to which academic degrees are awarded. The methods of comparison and data statistical analysis were applied to assess structural changes in the nomenclature.Results and scientific novelty. The authors considered the prerequisites for update of the nomenclature of academic specialities approved in 2017. The features of a new edition of the nomenclature of academic specialities were highlighted. The analysis of its new structure and content changes was carried out. It is demonstrated that current network of dissertation councils (1696 councils) can be divided into 4 groups according to the degree of compliance of academic specialities and fields of science with the previous and recent versions of nomenclature. It is necessary to create new dissertation councils for 20 new academic specialities.Practical significance. The authors revealed the features of the new nomenclature, requiring the reorganisation of councils network for the defense of doctoral and candidate dissertations. On this basis, to provide promising areas of academic research, the proposals on the implementation of new nomenclature provisions are outlined. The stages of re-opening of dissertation councils network are described.